2022
DOI: 10.3389/fpsyg.2022.941235
|View full text |Cite
|
Sign up to set email alerts
|

Suffering doubly: Effect of cyberbullying on interpersonal deviance and dual mediating effects of emotional exhaustion and anger

Abstract: Research on employee harassment, in the form of workplace bullying, has increased over the past decade. However, there is little research on the prevalence and impact of cyberbullying, a type of cyber-related violence in the workplace. Thus, it would be interesting to examine the impact of cyberbullying on interpersonal deviance through the serial mediating effect of emotional exhaustion and anger. Drawing from the conservation of the resource theory and the affective event theory, this proposed study clarifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
1
0
0
Order By: Relevance
“…The multiple regression analysis identified several significant predictors of cyberbullying victimization among high school students, including the female gender, younger age, lower educational achievement, and higher daily use of the Internet. These findings are consistent with previous research that has identified demographic, academic, and internet usage factors as important predictors of cyberbullying experiences [ 98 , 99 , 100 , 101 ]. The identification of these risk factors has important implications for the development of targeted prevention and intervention strategies [ 38 , 102 ].…”
Section: Discussionsupporting
confidence: 92%
“…The multiple regression analysis identified several significant predictors of cyberbullying victimization among high school students, including the female gender, younger age, lower educational achievement, and higher daily use of the Internet. These findings are consistent with previous research that has identified demographic, academic, and internet usage factors as important predictors of cyberbullying experiences [ 98 , 99 , 100 , 101 ]. The identification of these risk factors has important implications for the development of targeted prevention and intervention strategies [ 38 , 102 ].…”
Section: Discussionsupporting
confidence: 92%